Do Horizontal Saccadic Eye Movements Increase Interhemispheric Coherence? Investigation of a Hypothesized Neural Mechanism Underlying EMDR - Samara, Zoe; Elzinga, Bernet M.; Slagter, Heleen A.; Nieuwenhuis, Sander (Frontiers in Psychiatry, 2011)
Series of horizontal saccadic eye movements (EMs) are known to improve episodic memory retrieval in healthy adults and to facilitate the processing of traumatic memories in eye-movement desensitization and reprocessing (EMDR) therapy. Several authors have proposed that EMs achieve these effects by increasing the functional connectivity of the two brain hemispheres, but direct evidence for this proposal is lacking. The aim of this study was to investigate whether memory enhancement following bilateral EMs is associated with increased interhemispheric coherence in the electroencephalogram (EEG). Fourteen healthy young adults were asked to freely recall lists of studied neutral and emotional words after a series of bilateral EMs and a control procedure. Baseline EEG activity was recorded before and after the EM and control procedures. Phase and amplitude coherence between bilaterally homologous brain areas were calculated for six frequency bands and electrode pairs across the entire scalp. Behavioral analyses showed that participants recalled more emotional (but not neutral) words following the EM procedure than following the control procedure. However, the EEG analyses indicated no evidence that the EMs altered participants’ interhemispheric coherence or that improvements in recall were correlated with such changes in coherence. These findings cast doubt on the interhemispheric interaction hypothesis, and therefore may have important implications for future research on the neurobiological mechanism underlying EMDR.